ANALISA FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU KARYAWAN KILANG PAPAN DALAM PENGGUNAAN ALAT PELINDUNG DIRI DI PT HIDUP BARU KOTA BINJAI TAHUN 2014 - Netty Jojor Aritonang (Poltekkes Kemenkes Medan, 2016)
Occupational health and safety is an attempt to guarantee safety and improve the health standard of workers by preventing them from accidence and illness caused by job, controlling danger in the job sites, and promoting health, medication, and rehabilitation. The use of personal protection equitment (PPE) is one of the efforts to decrease the incidence of health danger and job accidence. The objective of the research is to analyze some factors which influenced the behavior of lumber mill workers in using personal protection equitment at PT Hidup Baru, Binjai, in May, 2014. Cross sectional design was used to analyze some factors which influenced the behavior of lumber mill workers in using personal protection equitmentat PT Hidup Baru. The population was all 43 lumber mill workers. The data were analyzed by using chi square test and multiple logistic regression tests. The result of the research showed that there was the influence of the workers’ knowledge (p = 0.038) and attitude (p = 0.026) at PT Hidup Baru, Binjai, on the use of personal protection equitment. The variable of attitude had the most dominant influence on the use of PPE at Odds Ratio (OR) of 7,405 which indicated that the workers who had positive attitude had the opportunity to use personal protection equitment 9.7,405 times than those who had negativeattitude. It is recommended that the management of the lumber mill, PT. Hidup Baru, Binjai, should improve the workers’ knowledge of the risk and provide facility of training about job health and safety for them and the workers improve their knowledge, attitude, and behavior about their job safety in their job.